2009
DOI: 10.1007/978-1-4419-0284-9_2
|View full text |Cite
|
Sign up to set email alerts
|

The Etiology of Osteosarcoma

Abstract: Studies to determine the etiology of osteosarcoma involve epidemiologic and environmental factors and genetic impairments. Factors related to patient characteristics include age, gender, ethnicity, growth and height, genetic and familial factors, and preexisting bone abnormalities. Rapidly proliferating cells may be particularly susceptible to oncogenic agents and mitotic errors which lead to neoplastic transformation. Genetic aberrations that accompany osteosarcoma have received increasing recognition as an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
172
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(179 citation statements)
references
References 55 publications
0
172
1
Order By: Relevance
“…Osteosarcoma can be caused by other types of cancer, including Li-Fraumeni syndrome (resulting from a p53 mutation), hereditary retinoblastoma (RB) and associated diseases caused by an RB mutation (13). Other internal or external factors can also contribute to the disease development (6,14). In the present study, the pathogenesis of osteosarcoma, with regard to the expression of COX-2 and miRNA-143 and the association between them, was investigated.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Osteosarcoma can be caused by other types of cancer, including Li-Fraumeni syndrome (resulting from a p53 mutation), hereditary retinoblastoma (RB) and associated diseases caused by an RB mutation (13). Other internal or external factors can also contribute to the disease development (6,14). In the present study, the pathogenesis of osteosarcoma, with regard to the expression of COX-2 and miRNA-143 and the association between them, was investigated.…”
Section: Discussionmentioning
confidence: 98%
“…At present, the exact mechanism of osteosarcoma pathogenesis is unclear. Certain studies have suggested that osteosarcoma can be induced by other types of cancer, as well as environmental stimuli to bone cells, such as toxins, viruses and radiation (5)(6)(7). In addition, disturbed hormone levels can increase the incidence of osteosarcoma, particularly in teenagers with excess hormone secretion (8).…”
Section: Introductionmentioning
confidence: 99%
“…Osteosarcoma (OS) is the most frequent primary malignant bone tumor in children and young adolescents (1,2). The survival rates for OS have improved considerably since the introduction of multi-agent chemotherapy in the 1980s, with a 5-year overall survival rate of 60-65% for patients without metastasis (3), and have remained relatively constant for the past two decades (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have sought to improve our understanding of osteosarcoma, and epidemiological studies have reported significant findings, such as the effects of puberty, disorders of bone growth and remodeling, and genetic predisposition (2)(3)(4). However, as with several types of cancer, the etiology of osteosarcoma remains unclear.…”
Section: Introductionmentioning
confidence: 99%